PERANCANGAN SISTEM ABSENSI GURU BERBASIS WEB MENGGUNAKAN METODE SDLC WATERFALL - Rosyida, Ayu; Junio, Fazel; Hermawan, Indra (MULTINETICS, 2021)
In the current era of globalization, the role of information technology is so large development, this makes many human jobs replaced by computerized system. After that the website can be used for system creation presence of teachers to improve discipline and teaching. During this time, the process attendance data recapitulation still uses books. However, in attendance still using the manual method, namely by initialing or the presence of a picket teacher. That matter can cause several obstacles such as having the risk of being lost or damaged, the occurrence of duplicate data, and will make it difficult to carry out the process presence data search. The method used by the author is Waterfall. Because of the above, the author wants to create a website which can be used to recapitulate teacher presence and time data inteach more efficiently. This website is built using a programming language PHP with Laravel framework and MySQL database along with several stages starting from planning, analysis, system design, display design, program coding, and testing. Making this website can computerize the attendance process which was previously still using the system manually.The test results from Blackbox Testing are 100%, UAT testing is 97% and SUS testing is getting a value of 73.5. So it can be concluded that the website-based attendance application has been successful